Detection of SYT-SSX mutant transcripts in formalin-fixed paraffin-embedded sarcoma tissues using one-step reverse transcriptase real-time PCR - A.Talib, Norlelawati; Goon, Mohd Danial; Harun, Nora; Othman, Nadia; Kamaruzaman, Zatur Rawihah; Abdullah, Nor Zamzila; Muhammad, Siti Aeshah @ Naznin (College of Pathologists, Academy of Medicine Malaysia, 2016)
Background: Synovial sarcoma (SS) is a rare cancer and accounts for 5-10% of adult soft tissue sarcomas. Making an accurate diagnosis is difficult due to the overlapping histological features of SS with other types of sarcomas and the non-specific immunohistochemistry profile findings. Molecular testing is thus considered necessary to confirm the diagnosis since more than 90% of SS cases carry the transcript of t(X;18)(p11.2;q11.2). The purpose of this study is to diagnose SS at molecular level by testing for t(X;18) fusion-transcript expression through One-step reverse transcriptase real-time Polymerase Chain Reaction (PCR). Method: Formalin-fixed paraffin-embedded tissue blocks of 23 cases of soft tissue sarcomas, which included 5 and 8 cases reported as SS as the primary diagnosis and differential diagnosis respectively, were retrieved from the Department of Pathology, Tengku Ampuan Afzan Hospital, Kuantan, Pahang. RNA was purified from the tissue block sections and then subjected to One-step reverse transcriptase real-time PCR using sequence specific hydrolysis probes for simultaneous detection of either SYT-SSX1 or SYT-SSX2 fusion transcript. Results: Of the 23 cases, 4 cases were found to be positive for SYT-SSX fusion transcript in which 2 were diagnosed as SS whereas in the 2 other cases, SS was the differential diagnosis. Three cases were excluded due to failure of both amplification assays SYT-SSX and control β-2-microglobulin. The remaining 16 cases were negative for the fusion transcript. Conclusion: This study has shown that the application of One-Step reverse transcriptase real time PCR for the detection SYT-SSX transcript is feasible as an aid in confirming the diagnosis of synovial sarcoma.